IDENTIFIKASI TUMBUHAN PIONIR DI AREA BEKAS TAMBANG BIJI BESI DESA PULAU LAYANG, KECAMATAN BATANG MASUMAI - Joko Pramuseto; Leni Marlina; Rozana Zuhri (Pendidikan Biologi STKIP YPM Bangko, 2020)
This research was motivated by the absence of data on pioneer plants that grew in the former iron ore mining area in PulauLayang Village, BatangMasumai District. In addition, there is still a lack of data and research on pioneer plants in Merangin Regency. The purpose of this study was to identify and identify the types of pioneer plants in the former iron ore mining area of ​​PulauLayang Village, BatangMasumai District. This type of research is exploratory research with a descriptive approach. The sampling technique used was purposive random sampling technique. From the results found after the examination, 13 species were found from the three plots, where in the first plot 6 species were found, in the second plot 6 species were found, and from the third plot, 6 species. Overall species found wereAlstonia iwahigensis, Blenchnum orientale, Imperata cylindrica, Lycopodium cernuum, Melastoma malabathricum, Pennisetum purpureum, Pteridium aquilinum, Dicranopteris linearis, Merremia peltata, Carex muskingumensis, Caryocar glabrum, Ipomoea purpurea, and Breynia vitis-idaea. The dominating species was Imperatacylindrica which was found as many as 224, the least was found was Alstoniaiwahigensis which was found only 1 species